Metacognitions about Consumer Protection and Individual Responsibility in the Credit Card Domain. (April 2013) - Henry, Paul; Garbarino, Ellen; Voola, Ranjit
This article explores how everyday consumers form opinions about consumer protection and individual responsibility in the credit card domain. A startling lack of research on the consumer perspective motivates this current project. Using secondary documents, the authors identify the contributing factors of (1) distrust of card providers, (2) attribution of blame to people experiencing credit card difficulties, (3) perceptions of inherent human fallibility, (4) belief that credit card use can cause financial misery, (5) sympathy toward those experiencing credit card difficulties, and (6) negative experience of card debt. They operationalize and assess these factors using an online survey. They then employ structural equation modeling analysis to explore the relationships among these six factors and to responsibility and protection beliefs. Finally, they discuss implications for consumer advocates, public policy makers, and others who aim to change consumers' beliefs about consumer protection and individual responsibility.